Strategi Pencegahan Diare pada Anak Melalui Perilaku Hidup Bersih dan Sehat (PHBS) untuk Mengurangi Risiko Stunting di Pondok Pesantren Al-Hidayah Kabupaten Seluma - Nurhayati, Rahmi; Fauzi , Yusran; Dwiyantara , Jimmi; Wulandari , Sri (Utami Publisher, 2025)
Diarrheal disease is one of the leading causes of morbidity and mortality among children, particularly in areas with poor environmental hygiene. In Sukasari Village, Air Periukan Subdistrict, Seluma Regency, the incidence of diarrhea remains high and contributes to the risk of stunting. The 2025 Thematic Community Service Program (KKN-T) by Dehasen University Bengkulu aimed to improve community knowledge and practices in preventing diarrhea through educational approaches. The strategies implemented included counseling on diarrhea and Clean and Healthy Living Behavior (PHBS), demonstrations on proper handwashing techniques, distribution of educational leaflets, and the use of digital media. The program was conducted at Al-Hidayah Islamic Boarding School in collaboration with village officials and local residents. The results showed increased awareness among students and teachers regarding personal and environmental hygiene. This initiative proved effective in reducing diarrhea cases and served as a preventive measure against stunting in children. Cross-sector collaboration and continuous education are essential in building a healthy and self-reliant community.